A framework of the value creation process in public-private partnerships (PPPS) - Namirembe, Hudah Bawonga (Rhodes University, 2026)
Governments worldwide have adopted Public Private Partnership projects (PPP projects) as a tool to create value for stakeholders in society, amidst funding constraints. Under the PPP arrangement, the government, representing itself and the general public, partners with the private sector and delegates part of its responsibilities to the private partner, while at the same time leveraging shared resources to deliver public products and services. Both partners, therefore, invest heavily in this partnership to deliver products and services in different sectors of the economy, thus creating value for stakeholders. Evidence through a review of literature shows that whereas many countries have adopted PPPs as a mode of project delivery, in some contexts PPP projects have successfully created value for stakeholders, while in other contexts, they have failed. Generally, PPPs are attributed to improvement of service delivery and stakeholder satisfaction. Therefore, this failure is attributed to barriers within the current practices of the projects within the phases of the PPP Project Lifecycle (PPP-PLC) which hinder the value creation process. These failures have far-reaching effects which have over time been reported as public unrest, riots, project stagnation, project termination, project breakdowns and heavy losses. And, in some economies, the PPP mode of project delivery has been disbanded altogether. Yet, despite stakeholders' efforts to improve the value creation process, little is known about how successful PPP projects have over time within some economies created value while others failed within the same economy and outside. A number of justifications have been theorised about their failure and success in value creation. However, there is no framework developed to guide project stakeholders through the phases of the PPP-PLC to successfully create value. The study therefore set out to develop a best practice value creation framework for PPP projects by answering the MRQ: “How is value created in PPP projects in Uganda’s economy?” The aim of this thesis therefore is to examine how value is created in PPP projects in Uganda’s landscape with the goal of developing and validating a best practice value creation framework that addresses the barriers, leverages the drivers and incorporates current and best practices across the PPP-PLC in the creation of value. The study, underpinned by Public Value Theory, examined PPP projects, from the Ugandan perspective to answer this research question. The study, guided by research sub questions adopted a qualitative research method to collect and analyse data from sixteen (16) participants from among PPP projects in Uganda. Using a purposive sampling technique, the study selected participants from among the stakeholders of PPP projects. The sample population was drawn from among project managers and end users who were directly involved in the PPP projects. The study adopted a cross-sectional time horizon to collect and analyse data. To collect data, the study used the interview technique that allowed the interviewer to interact directly with the participants. The participants were interviewed through Key Informant Interviews (KIIs) using a semi- structured interview guide. The interviews were conducted through different interview modes including, online, face-to-face, and by telephone. The study collected and analysed data concurrently until point of saturation. The collected data was analysed using Atlas. Ti-24 software in line with the research sub-questions and research propositions. The study thus made a theoretical contribution by presenting a best practice value creation framework for PPP projects. Underpinned by the PV theory the study made theoretical contributions by aligning projects and resources to stakeholder needs and expectations in the creation of value.
a perspective of Ugandan projects
Keywords: Uncatalogued